(untitled) (SAARC Journal of Agriculture, 2015)
Development of varieties with high yield potential coupled with wide adaptability is an important plant breeding objective. Presence of genotype and environment (G×E) interaction plays a crucial role in determining the performance of genetic materials, tested in different locations in different years. This study was under taken to assess yield performance, stability and adaptability of seventeen hybrid rice genotypes evaluated over 12 environments. The analysis of variance for growth duration and grain yield (t ha-1) for genotype, environment year, environment × genotype, year × environment, year × genotype and year × environment × genotype were highly significant (p<0.01) showing the variable response of the genotype across environments and year. GE interaction patterns revealed by AMMI biplot analysis indicated that the hybrid rice genotypes are broadly adapted. Genotypes BRRI53A/BRRI26R, Jin23A/507R, Jin23A/BR7881-25-2-3-12 and IR79156A/F2277R were best for the environment: Gazipur and Rangpur at second and third year. Genotypes Jin23A/PR344R, BRRI11A/AGR and IR79156A/BRRI20R showing high yield performance and widely adapted to all environments. DOI: http://dx.doi.org/10.3329/sja.v12i2.21912 SAARC J. Agri., 12(2): 1-15 (2014)